Flowsheet simulation of aqueous two-phase extraction systems for protein purification - Ahmad, Murni M (John Wiley & Sons, Ltd., 2010)
BACKGROUND: Aqueous two-phase extraction (ATPE) has many advantages as an efficient, inexpensive large-scale liquid–liquid extraction technique for protein separation. However, the realization of ATPE as a protein separation technology at industrial scales is rather limited due to the large, multidimensional design space and the paucity of design approaches to predict phase and product behavior in an integrated fashion with overall system performance. This paper describes a framework designed to calculate suitable flowsheets for the extraction of a target protein from a complex protein feed using ATPE. The framework incorporated a routine to set up flowsheets according to target protein partitioning behavior in specific ATPE systems and a calculation of the amounts of phase-forming components needed to extract the target protein. The thermodynamics of phase formation and partitioning were modeled using Flory-Huggins theory and calculated using a Gibbs energy difference minimization approach.